Liberation Theologies and Their Future: Rethinking Categories and Popular Participation in Liberation - Rieger, Joerg (Religions, 2023)
The first generation of Latin American liberation theologies was marked by the methodological status of the preferential option for the poor. In the following generations, this commitment was further developed in the struggle for a new way of doing theology, even more connected to material life, and disciplines such as history and economics were added. With this, the organizational structures of life in society started to be discussed in more critical, systemic, and prophetic ways. Especially thinking of the Latin American and US contexts, the production of theology derived from this intersectionality seeks not only to highlight and analyze the economic structures that cause exploitation (class), inequalities (gender and sexuality), and racism, but to identify how religion undergirds solidarity movements. The method applied to discuss these themes is bibliographical research. As a broad conclusion, this article indicates that future liberation theologies should discuss what the multiple victims of capitalism (always the majority of the population, never merely a minority) do in order to survive, related to the alternatives they create; discuss solidarity as the foundation that opposes social evil; and discuss the illusions of individualism that cover up both existing relationships of exploitation as well as solidarity.